Ethnic Cleansing and Genocidal Intent: Conceptualizing Destruction of Local Populations - Hannibal Travis (Washington University Global Studies Law Review, 2021)
Atrocities against an identifiable group may qualify as genocide even though most members of the group take flight and the group survives the campaign against it. This type of scenario, widely known as "ethnic cleansing," may lead to an inference of genocidal intent because of the atrocities themselves, statements reflecting religious or ethnonational hatred, disruption of family and communal life, and other patterns involving the targeting of group members and discrimination against them. Drawing on political philosophy as well as seventy-five years of domestic and foreign jurisprudence, this article proposes a "lifeworld"-based approach to genocidal intent. This approach explains and justifies the outcome in several decisions over the past decade involving prominent accusations of genocide, namely in Darfur, Srebrenica, the municipalities of Bosnia and Herzegovina, and Cambodia. A lifeworld-based approach asks whether an ethnic cleansing campaign left the targeted group without a viable homeland in which to exist and thrive. If the accused's actions are consistent with depriving the group of the means to perpetuate itself in the relevant locality, courts infer genocidal intent even if the entire group was not killed as soon as practicable, and even if a major component of the group was not killed. As the ad hoc tribunals in The Hague and the hybrid tribunal in Phnom Penh wrap up their cases on genocide and other international crimes, it is an opportune time to revisit the social and legal concept of genocide. Contrasting several potential approaches to genocidal intent, the article illustrates why international criminal tribunals during the last decade have gravitated toward a broader view of an "intent to destroy" a group "in whole or in part." Policies that persecute and discriminate against a group in a locality, such as a city, region, or province, may include one or more of the acts listed in the Article II of the UN Convention on the Prevention and Punishment of the Crime of Genocide and Article 6 of the Rome Statute of the InternationalCriminalCourt. The text and drafting history of Article II of the Convention -as well as state practice in enforcing and implementing it- lead judges to conclude that genocidal intent may be inferred from such policies. Mass killing, infliction of trauma and fear prompting widespread flight of displaced persons, deprivation of homes and livelihoods, separation of families, and interruption of both physical and cultural reproduction justify inferences of genocidal intent. They are also the patterns of atrocity that exemplify ethnic cleansing. The diplomats and jurists who abstractly defined the crime of genocide, as well as the prosecutors and judges who applied it to concrete cases, have clarified that genocide's "intent to destroy" does not require a total genocide or whole-group targeting. This article surveys the relevant jurisprudence of, among other courts and tribunals, the International Criminal Court, the International Court of Justice, the International Criminal Tribunal for the FormerYugoslavia, the ExtraordinaryChambers of the Courts of Cambodia, and the United States, German, Bosnian, and Iraqi courts.
Keywords: treaty interpretation; genocidal intent; intent to destroy; Genocide Convention; Rome Statute; United States Code; international criminal courts; ad hoc tribunals; hybrid tribunal